39AR-40AR AGE OF THE IBITIRA EUCRITE AND CONSTRAINTS ON THE TIME OF PYROXENE EQUILIBRATION - Bogard D.D.; Garrison D.H. (My University, 1995)
We determined a 39Ar-40Ar age of 4.495 +/- 0.015 Ga for the unbrecciated Ibitira eucrite. This age ranks among the oldest 39Ar-40Ar ages for eucrites and suggests that Ibitira escaped the widespread impact resetting of K-Ar ages ?4.1-3.5 Ga ago indicated by other HED meteorites. Ibitira exhibits a relatively high degree of chemical equilibration of its pyroxene caused by prolonged annealing. This equilibration must have occurred subsequent to the reported 207Pb-206Pb formation age for Ibitira of 4.556-4.560 Ga, but prior to its determined Ar-Ar age. If pyroxene equilibration occurred during burial at significant depths or in a large impact deposit, then the Ar-Ar age may date this event.